Representasi Maskulinitas dalam Iklan Kahf Versi Wajah Cerah dan Berenergi - Handayani, Fadila; Fadhil , Azfa Akbar; Widyatmoko, R. Nanang (Universitas Muhammdiyah Yogyakarta, 2025)
This study investigates the representation of masculinity in Kahf's “Wajah Cerah dan Berenergi” advertisement. This study analyses how the advertisement portrays the image of a modern man who cares about appearance and health, defying traditional stereotypes of masculinity. This is done using Roland Barthes' semiotic approach. The denotative and connotative in the images and text of the ad can be understood through a qualitative descriptive approach. Results show that this advertisement not only promotes the product but also demonstrates a shift in social norms about male identity, where self-care is considered a strong and positive component of masculinity. This study enhances our understanding of gender representation in the media.